On the Origin of Superoxide Dismutase: An Evolutionary Perspective of Superoxide-Mediated Redox Signaling - Adam J. Case (MDPI AG, 2017)
The field of free radical biology originated with the discovery of superoxide dismutase (SOD) in 1969. Over the last 5 decades, a plethora of research has been performed in species ranging from bacteria to mammals that has elucidated the molecular reaction, subcellular location, and specific isoforms of SOD. However, while humans have only begun to study this class of enzymes over the past 50 years, it has been estimated that these enzymes have existed for billions of years, and may be some of the original enzymes found in primitive life. As life evolved over this expanse of time, these enzymes have taken on new and different functional roles potentially in contrast to how they were originally derived. Herein, examination of the evolutionary history of these enzymes provides both an explanation and further inquiries into the modern-day role of SOD in physiology and disease.